Xanthones Active against Multidrug Resistance and Virulence Mechanisms of Bacteria - Fernando Durães; Diana I. S. P. Resende; Andreia Palmeira; Nikoletta Szemerédi; Madalena M. M. Pinto; Gabriella Spengler; Emília Sousa (MDPI AG, 2021)
The emergence of multidrug and extensively drug-resistant pathogenic bacteria able to resist to the action of a wide range of antibiotics is becoming a growing problem for public health. The search for new compounds with the potential to help in the reversion of bacterial resistance plays an important role in current medicinal chemistry research. Under this scope, bacterial efflux pumps are responsible for the efflux of antimicrobials, and their inhibition could reverse resistance. In this study, the multidrug resistance reversing activity of a series of xanthones was investigated. Firstly, docking studies were performed in the AcrAB-TolC efflux pump and in a homology model of the NorA pump. Then, the effects of twenty xanthone derivatives on bacterial growth were evaluated in Staphylococcus aureus 272123 and in the acrA gene-inactivated mutant Salmonella enterica serovar Typhimurium SL1344 (SE03). Their efflux pump inhibitory properties were assessed using real-time fluorimetry. Assays concerning the activity of these compounds towards the inhibition of biofilm formation and quorum sensing have also been performed. Results showed that a halogenated phenylmethanamine xanthone derivative displayed an interesting profile, as far as efflux pump inhibition and biofilm formation were concerned. To the best of our knowledge, this is the first report of xanthones as potential efflux pump inhibitors.